Water Conservation with Rainwater Harvesting System in Lampung Province (Case Study in State Polytechnic of Lampung Campus Area) - Aniessa Rinny Asnaning; . Surya; Andy Eka Saputra; Destieka Ahyuni (Journal of Science and Applicative Technology, 2019)
The excessive quantity of groundwater utilization leads to significantly reduced groundwater availability. In another aspect of a tropical country, Indonesia has a reasonably high rainfall in the rainy season. The problem of this research is that the rainwater that has not been utilized and managed to maximize so that only becomes runoff. The community can utilize rainwater for the daily need. This paper presents methods and prototypes of rainwater harvesting and collection at the research locus. Methods of rainwater collection can be done with a rainwater harvesting system in the form of gutter mounted on the roof of the building as a tool to direct the flow of rainwater on the roof to the shelter. Rainfall compared to the roof area, will produce the volume of stored rainwater reservoir as a parameter. The novelty proposed in this study is the value and variable of water parameters in the case study of research implementation This case study was carried out in one of the buildings at Lampung State Polytechnic. The building has 96.72 m2 of roof area with daily average rainfall equal to 8.6 mm/day (January to May 2018 period). Hence rainwater potency which can be accommodated per day by society is equal to 0.582 m3/month with assumption only 70% water rain that collected because of water loss. In the rainy season, the volume of actual rainwater that can be collected as much as 0,831 m3/month by ignoring water loss due to evaporation. The quality of rainwater analyzed based on several parameters is pH 4.4, temperature 27,5 oC, turbidity 2.02 NTU, total dissolved solids 20.48 ppm, iron <0.110 ppm, calcium 3.36 mg/l, magnesium 0.233 mg/l, lead <0,021 ppm, hardness 3.69 mg/l, and total coliform 6,1 CFU/100 ml. Testing of the results of this study conducted by testing water quality standards compliance with the regulation of the Indonesia Health Minister number 32 of 2017. Test results show that rainwater can be directly utilized for sanitary hygiene purposes with the improvement of pH value.